Influence of Two Major Toxoplasma Gondii Virulence Factors (ROP16 and ROP18) on the Immune Response of Peripheral Blood Mononuclear Cells to Human Toxoplasmosis Infection - Hernández-de-los-Ríos, Alejandro; Murillo-Leon, Mateo; Mantilla-Muriel, Luz Eliana; Arenas, Ailan Farid; Vargas-Montes, Mónica; Cardona, Néstor; de-la-Torre, Alejandra; Sepúlveda-Arias, Juan Carlos; Gómez-Marín, Jorge Enrique (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii ROP16 and ROP18 proteins have been identified as important virulence factors for this parasite. Here, we describe the effect of ROP16 and ROP18 proteins on peripheral blood mononuclear cells (PBMCs) from individuals with different clinical status of infection. We evaluated IFN-γ, IL-10, and IL-1β levels in supernatants from PBMCs cultures infected with tachyzoites of the T. gondii wild-type RH strain or with knock-out mutants of the rop16 and rop18 encoding genes (RHΔrop16 and RHΔrop18). Cytokine secretion was compared between PBMCs obtained from seronegative individuals (n = 10), with those with chronic asymptomatic (n = 8), or ocular infection (n = 12). We also evaluated if polymorphisms in the genes encoding for IFN-γ, IL-10, IL-1β, Toll-like receptor 9 (TLR9), and purinoreceptor P2RX7 influenced the production of the encoded proteins after ex vivo stimulation. In individuals with chronic asymptomatic infection, only a moderate effect on IL-10 levels was observed when PBMCs were infected with RHΔrop16, whereas a significant difference in the levels of inflammatory cytokines IFN-γ and IL-1β was observed in seronegative individuals, but this was also dependent on the host's cytokine gene polymorphisms. Infection with ROP16-deficient parasites had a significant effect on IFN-γ production in previously non-infected individuals, suggesting that ROP16 which is considered as a virulence factor plays a role during the primary infection in humans, but not in the secondary immune response.